The Stability of Vitamins D and K of the Human Brain During Freezer Storage: The Memory and Aging Project (MAP). (29th May 2020) - Fu, Xueyan; Shea, M Kyla; Dolnikowski, Gregory; Dawson-Hughes, Bess; Morris, Martha; Holland, Thomas; Dhana, Klodian; Booth, Sarah
Abstract: Objectives: Vitamins D and K are present in human brain tissue, and evidence is emerging that these nutrients may have a role in neurodegenerative disease. Given the increasing interest in conducting analyses of archived brain samples, it is important to evaluate the stability of these nutrients in brain tissue over long-term storage. Therefore, we evaluated the influence of freezer storage time on vitamin D and vitamin K concentrations in human brain samples. Methods: Post-mortem brain samples were obtained from 500 participants in the Rush Memory and Aging Project (mean age 91 yrs, 71% female). At autopsy and brain dissection, the tissues were immediately frozen on brass plates atop dry ice then stored at −80 o C until analysis. Storage time was categorized in 1-year increments. Vitamin D [25(OH)D] and vitamin K [menaquinone-4 (MK4)] concentrations were measured in four regions (mid-temporal cortex, mid-frontal cortex, cerebellum, anterior watershed white matter) using LC/MS/MS and HPLC, respectively. We calculated the mean 25(OH)D and MK4 concentrations across the four regions and then applied a natural-log transformation to the means to improve normality. Analysis of variance was used to determine if the geometric mean ± SEM 25(OH)D and MK4 concentrations differed according to storage time. The samples stored ≤1.0 year served as the reference group. Results: The mean 25(OH)D concentration in brains stored >6.0 years ( n  = 203; 0.8 ± 0.05 pmol/g), was significantly lower than the concentration in brains stored ≤1.0 year ( n  = 79; 1.2 ± 0.09 pmol/g, P  ≤ 0.004). The 25(OH)D in the brains stored ≤1.0 year did not differ from the concentration in brains stored for 1.1–6.0 years ( n  = 212; 1.2 ± 0.05 pmol/g, P  ≥ 0.37). The mean MK4 concentration in the brains stored ≥9.0 years ( n  = 81; 0.7 ± 0.6 pmol/g) was significantly lower than that in the brains stored ≤1.0 year (1.2 ± 1.3 pmol/g; P  ≤ 0.01). The MK4 in brains stored ≤1.0 year did not differ from the concentration in brains stored for 1.1–9.0 years ( n  = 339; 1.3 ± 0.8 pmol/g; P  ≥ 0.11). Conclusions: 25(OH)D and MK4 appear to be stable in brain tissue stored at −80 °C for up to 6 and 9 years, respectively, but not longer. This should be considered in the design and interpretation of studies linking brain concentrations of these nutrients to neurodegenerative diseases. Funding Sources: Supported by the National Institute of Aging.